THE EFFECTIVENESS OF HEALTH EDUCATION METHOD ON EARLY DETECTION CARCINOMA MAMMAE IN TEENAGE GIRLS OF MADRASAH ALIYAH IN MIJEN SUB-DISTRICT - Yuslikhah, Aronida Mutia; Wijayanti, Yuni; Rustiana, Eunike Raffy (Universitas Negeri Semarang, 2019)
Carcinoma Mammae or Breast Cancer is a type of malignant tumor which is the number one killer for women. In Semarang, there were 1182 new cases in 2017, this number increased from 2016 which was 749 cases of breast cancer. This research aims to analyze the level of effectiveness of health education between video media and demonstration methods on changes in knowledge, attitudes, and behavior of independent early detection of carcinoma mammae in teenage girls of Madrasah Aliyah in Mijen Sub-District. This research is a quantitative research using the Quasi-Experiment method with pre-test post-test design. The research sample was 130 respondents with purposive sampling technique. The instrument was a research questionnaire and observation sheet. The results showed that health education with a demonstration method was more effective on changes of knowledge (p-value 0.022), attitudes (p-value 0.041), and behavior (p-value 0.036) in independent early detection of carcinoma mammae in teenage girls of Madrasah Aliyah in Mijen Sub-District. Whether a change occurs or not is related to the stimulus given to someone. Training is a part of education which is related to the learning process to improve skills in a relatively short period and also through methods which prioritize practice (demonstration) rather than theory.Ã‚Â